2015
DOI: 10.1111/jfs.12239
|View full text |Cite
|
Sign up to set email alerts
|

Growth Potential Assessment of Listeria in Milk Fat Products by Challenge Testing

Abstract: Milk fat products (MFP), including butter and low-fat dairy spreads, are a specific type of ready-to-eat food known as water-in-fat emulsions, in which the behavior of microbial foodborne pathogens such as Listeria monocytogenes is not clearly known. This study investigated the growth and survival of L. monocytogenes, and of Listeria innocua as a surrogate for L. monocytogenes, in these foods using challenge testing. Three commercial MFPs with various fat contents (butter, half butter and low-fat dairy spread)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
(42 reference statements)
1
8
0
Order By: Relevance
“…The results relative to the growth of L. monocytogenes in butter were in accordance with those reported by Michelon et al (2016) who observed no growth of the pathogen in the tested samples of churned butters and commercial milk fat products (pH < 5.80). The levels of the bacterium remained however stable during shelf life.…”
Section: Discussionsupporting
confidence: 91%
“…The results relative to the growth of L. monocytogenes in butter were in accordance with those reported by Michelon et al (2016) who observed no growth of the pathogen in the tested samples of churned butters and commercial milk fat products (pH < 5.80). The levels of the bacterium remained however stable during shelf life.…”
Section: Discussionsupporting
confidence: 91%
“…Several recent studies have focused on the growth potential of L. monocytogenes in different RTE food products (Awaiwanont, Smulders, & Paulsen, 2015;Coroneo et al, 2016;Dalzini et al, 2014;Grassi, Nucera, Lomonaco, & Civera, 2013;Jesus et al, 2016;Lahou & Uyttendaele, 2017;Michellon et al, 2016;Sahu, Kim, Ferguson, Zink, & Datta, 2017;Sant'Ana, Barbosa, Destro, Landgraf, & Franco, 2012;Skalina & Nikolajeva, 2010;Spanu et al, 2012;Uyttendaele et al, 2009). These studies intended the classification of foods in the appropriate food category specified in Reg.…”
Section: Resultsmentioning
confidence: 99%
“…That allows having smaller moisture droplets, which is important for the keeping quality of butter as it limits the growth of microorganisms (Michelon et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…In literature, slightly overworking butter is preferred to underworking and increased speed preferred to working at slow speed (Walstra et al 2006). That allows having smaller moisture droplets, which is important for the keeping quality of butter as it limits the growth of microorganisms (Michelon et al 2016).…”
Section: Butter Productionmentioning
confidence: 99%